An image guided adaptive radiotherapy strategy for cervix cancer treatment based on equivalent uniform dose - O’Reilly, Frederika Hendrika Jacoba (University of the Free State, 2021)
Aim: This study aims to develop an image-guided adaptive strategy to compensate for temporal effects of tumour shrinkage and organ motion in cervix cancer treatment based on the equivalent uniform dose (EUD). The strategy should be flexible enough to retain a minimum workload system. Materials and Methods: Patients receiving radical radiotherapy treatment for cervix cancer with daily pre-treatment CBCT imaging were included in this retrospective study. A thorough investigation of bladder volume variation and its influence on primary and nodal tumor motion using both empty and full bladder protocols during cervix cancer RT was performed. 6 treatment strategies; fixed margins (7, 10, 15, and 20 mm), offline and online adaptive ART strategies, an ITV approach, variable margin (VBM) and coverage probability (CoVP) strategy were simulated for both groups. Planning strategies were scored based on the equivalent uniform and dose volume histogram parameters. Results and Discussion: Although empty bladder volumes were more reproducible no significant difference in movement between EB and FB patients was observed. Our study confirmed dosimetric advantages in bladder and small bowel sparing when a full bladder protocol is used. Occupancy probability maps were used to quantify primary and nodal movement. The best target coverage and OAR sparing were seen when online and offline adaptive strategies were used. Fixed margins <10 mm caused underdosages in most patients. Although adequate target coverage was noted for the ITV and VBM strategy, OAR sparing was inferior. CovP planning resulted in dosimetric outcomes similar and even better than the online strategy. Conclusion: Considering bladder volume reproducibility and protocol executability, an empty bladder protocol appears simpler in our department. However, variations in target shape and position cannot be attributed to bladder filling alone. The EUD can be used as a quick and reliable way of scoring treatment plans. Based on EUD metrics this study demonstrated that a personalized on-line adaptive strategy is most effective to account for target motion and deformation, yielding sufficient target coverage with adequate OAR sparing.
Thesis (Ph.D. (Physics))--University of the Free State, 2021
Keywords: Image guided adaptive radiotherapy; Equivalent uniform dose; Cervical cancer; External beam radiotherapy; Treatment planning; Coverage probability